Mediation, Peacekeeping, and the Severity of Civil War. (August 2019) - Beardsley, Kyle; Cunningham, David E.; White, Peter B.
One of the proposed benefits of third-party involvement that has been offered to justify its use is that it helps reduce the severity of conflict. Existing work finding that peacekeeping operations reduce battle-related fatalities considers peacekeeping in isolation from other forms of third-party diplomatic involvement, such as mediation. We argue that mediation has its own effect on patterns of violence. Moreover, we argue that peacekeeping and mediation can have an interactive effect, in which each enhance the violence-reducing potential of the other. Using monthly data on battle-related deaths in African intrastate conflicts, we find that mediation is associated with reduced bloodshed. We also find, consistent with existing work, that a greater number of peacekeepers leads to a reduction in violence. In addition, we find that mediation and peacekeeping efforts reinforce one another, although each type of involvement is able to reduce battlefield fatalities independently.